The literature of leisure and Chinese modernity - Laughlin, Charles A (University of Hawai'i Press, 2008)
Ebook from IG Library; Includes bibliographical references and indexes; The Chinese essay is arguably China’s most distinctive contribution to modern world literature, and the period of its greatest influence and popularity—the mid-1930s—is the central concern of this book. What Charles Laughlin terms "the literature of leisure" is a modern literary response to the cultural past that manifests itself most conspicuously in the form of short, informal essay writing (xiaopin wen). Laughlin examines the essay both as a widely practiced and influential genre of literary expression and as an important counter-discourse to the revolutionary tradition of New Literature (especially realistic fiction), often viewed as the dominant mode of literature at the time. After articulating the relationship between the premodern traditions of leisure literature and the modern essay, Laughlin treats the various essay styles representing different groups of writers. Each is characterized according to a single defining activity: "wandering" in the case of the Yu si (Threads of Conversation) group surrounding Lu Xun and Zhou Zuoren; "learning" with the White Horse Lake group of Zhejiang schoolteachers like Feng Zikai and Xia Mianzun; "enjoying" in the case of Lin Yutang’s Analects group; "dreaming" with the Beijing school. The concluding chapter outlines the impact of leisure literature on Chinese culture up to the present day.The Literature of Leisure and Chinese Modernity dramatizes the vast importance and unique nature of creative nonfiction prose writing in modern China. It will be eagerly read by those with an interest in twentieth-century Chinese literature, modern China, and East Asian or world literatures